A SWOT analysis of innovative high sustainability pavement surfaces containing crumb rubber modifier. (14th September 2020) - Leandri, P.; Rocchio, P.; Losa, M.
Abstract : In order to compare some innovative solutions of sustainable pavement surfaces containing crumb rubber modifier (CRM), a strengths, weaknesses, opportunities, and threats (SWOT) analysis of different technologies developed for production of low noise pavements (LNPs) has been carried out. CRM is one of the by-products obtained from end-of-life tyres (EOLT) that is currently recycled in asphalt pavements worldwide, with different technologies and more interest in some countries compared to others. In order to demonstrate the effective use of CRM in LNP, the project NEREIDE was funded by the EC in 2017 within the framework of LIFE projects, with the specific aim of developing innovative solutions for sustainable LNP with CRM, by using both the wet and the dry process. In the Phase I of the NEREiDE project, the mechanical and functional performances of the new LNP surfaces, developed by using the two technologies, were analysed and compared in order to assess their respective potentials for use as viable alternatives to other traditional LNP surfaces. The analysis of laboratory and on-site test results, carried out on specifically built field trials, allowed to understand strengths and weaknesses of the new LNPs in terms of mechanical and functional performance. In order to identify opportunities and threats in the analysis, the external factors that can be helpful or harmful to the recycling of CRM in LNPs have been analysed.